(untitled) (Research, Society and Development, 2025)
This article aims to analyze the relationship between body awareness and integral human education in Federal Institutes, based on historical-dialectical materialism and the critical-overcoming approach. A literature review was conducted, using academic sources from the last five years, retrieved from databases such as SciELO, Elsevier, and Google Scholar. The study demonstrates that body awareness plays a fundamental role in shaping the historical subject, allowing individuals to understand their corporeality as an inseparable element of their identity and social relationships. Additionally, the research highlights that interdisciplinary pedagogical practices, such as integrative projects and active methodologies, significantly contribute to the development of students’ body perception, fostering their autonomy and critical engagement in society. However, challenges such as the reduction of physical education class hours and the imposition of neoliberal curricular models may hinder the effective implementation of this approach in Federal Institutes. It is concluded that valuing body awareness in integral human education is essential to ensure teaching that promotes students’ full development, preparing them to act critically and transformatively in society.